Study of uropathogenic Escherichia coli with special reference to its virulence factors - Kaira, Sanjay Singh; Pai, Chitra (International Journal Of Community Medicine And Public Health, 2017)
Background: Urinary tract infection (UTI) is one of the most common nosocomial infections, caused by Escherichia coli. UPEC differ from non-pathogenic E. coli by the production of specific virulence factors which enable the bacteria to adhere to uroepithelial cells and to establish UTI. The aim of this study is to check the virulence factors of uropathogenic E. coli. Methods: A prospective study conducted in the Department of Microbiology of a tertiary level hospital in Mumbai over a period of one year (February 2011 to February 2012). A total of 123 Urine samples received in the laboratory were processed as per standard microbiological procedures to look for virulence factors like hemolysin, hemagglutination, cell surface hydrophobicity and gelatinase production. Results: Out of 123 patients 69 (56.09%) cases were from females and 54 (43.90%) were males. Thus female: male ratio was 1:3. Hemolysin production was seen in 27.64%, hemagglutination in 53%, cell surface hydrophobicity in 27.64%. Conclusions: UTI is more common in middle aged females and in community set-up. The knowledge of virulence factors of E. coli will help in better understanding of the organism pathogenicity and guided empirical therapy can result in better treatment outcome.